Exploring the provision and motives behind the adoption of health-promotion programmes in professional football clubs across four European countries - Røynesdal, Ø. B.; van Nassau, F.; Chng, N. R.; Pereira, H.; Andersen, E.; Bunn, C.; Jelsma, J. G. M.; Nijhuis-van der Sanden, M. W. G.; Roberts, G. C.; Sørensen, M.; van de Glind, I.; van Actherberg, T.; et al. (PLOS ONE, 2021)
This study mapped existing health-promotion provisions targeting adults in professional football clubs across England, the Netherlands, Norway, and Portugal, and explored motives behind the clubs` adoption of the European Fans in Training (EuroFIT) programme. We surveyed top-tier football clubs in the four countries and interviewed representatives from football clubs and the clubs` charitable foundation who delivered EuroFIT. The findings showed large between-country differences, with football clubs in England reporting far greater healthy lifestyle provision than other countries. Relatively few health-promotion programmes targeted adults, particularly in the Netherlands, Portugal, and Norway. Club representatives reported that the motives for adopting the EuroFIT programme often involved adhering to both the social objectives of the football club or club`s foundation and business-related objectives. They viewed the scientific evidence and evaluation underpinning EuroFIT as helpful in demonstrating the value and potential future impact of both the programme and the clubs` wider corporate social responsibility provision.